2015
DOI: 10.1158/0008-5472.can-14-2852
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Exerts Potent Antifibrotic and Antitumor Activities in Mouse Models of Pancreatic Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a dense stromal fibroinflammatory reaction that is a major obstacle to effective therapy. The desmoplastic stroma comprises many inflammatory cells, in particular mast cells as key components of the PDAC microenvironment, and such infiltration correlates with poor patient outcome. Indeed, it has been hypothesized that stromal ablation is critical to improve clinical response in patients with PDAC. Ibrutinib is a clinically approved Bruton's tyrosine k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 35 publications
(36 reference statements)
3
88
0
Order By: Relevance
“…Sagiv-Barfi and colleagues (16) demonstrated that ibrutinib in combination with anti-PD-L1 antibody provoked strong host T-cell-mediated antitumor activity against various tumor types, including triple-negative breast cancer, which led to high response rates and suppression of metastases. Others have reported ibrutinib modulation via BTK inhibition of myeloid-derived suppressor (17) or mast cells (18) in various solid tumor models. Our enzymatic and cellular assays indicated that the potential for such activities based on ITK and BTK inhibition were relatively unique for ibrutinib compared with other ERBB kinase family inhibitors studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sagiv-Barfi and colleagues (16) demonstrated that ibrutinib in combination with anti-PD-L1 antibody provoked strong host T-cell-mediated antitumor activity against various tumor types, including triple-negative breast cancer, which led to high response rates and suppression of metastases. Others have reported ibrutinib modulation via BTK inhibition of myeloid-derived suppressor (17) or mast cells (18) in various solid tumor models. Our enzymatic and cellular assays indicated that the potential for such activities based on ITK and BTK inhibition were relatively unique for ibrutinib compared with other ERBB kinase family inhibitors studied.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrutinib in combination with anti-PD-L1 antibody was shown to provoke strong host T-cell-mediated antitumor activity against various tumor types (16). Inhibition of BTK by ibrutinib has been suggested to be beneficial in some models by modulating myeloid-derived suppressor cells (17) and mast cells (18). Thus, if ibrutinib has clinically meaningful HER2-targeting activity, its effectiveness could be augmented by such modulation of the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that ibrutinib is an effective mast cell inhibitor and treatment of insulinoma‐bearing mice with this drug blocks mast cell degranulation and triggers collapse of tumour vasculature, tumour hypoxia and regression 23. In a preclinical model of pancreatic ductal adenocarcinoma as well as in patient‐derived xenograft‐models, ibrutinib showed mast cell dependent, antifibrotic activity and improved survival 24. Based on this finding, it was also suggested that the use of ibrutinib could potentially be extended to the treatment of other fibrotic diseases or chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…As FDA-approved B cell-targeting agents already exist (Kipps et al, 2017), their potential for the treatment of pancreatitis could be rapidly evaluated. Notably, the BTK inhibitor ibrutinib improved survival rates in mouse models of pancreatic cancer (Gunderson et al, 2016; Masso-Valles et al, 2015), and B cell-targeted approaches could thus have beneficial actions on both pancreatitis and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%